2018
DOI: 10.1056/nejmoa1705835
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Glucocorticoid Therapy in Patients with Septic Shock

Abstract: Among patients with septic shock undergoing mechanical ventilation, a continuous infusion of hydrocortisone did not result in lower 90-day mortality than placebo. (Funded by the National Health and Medical Research Council of Australia and others; ADRENAL ClinicalTrials.gov number, NCT01448109 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
649
5
14

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 722 publications
(733 citation statements)
references
References 35 publications
14
649
5
14
Order By: Relevance
“…Total mortality consequently was 46.1%. In contrast, one study did not show a benefit with corticosteroid administration . Inclusion criteria for this study required any vasopressor use for a minimum of 4 hours, and total mortality rate was 28.3%.…”
Section: Corticosteroidsmentioning
confidence: 90%
See 1 more Smart Citation
“…Total mortality consequently was 46.1%. In contrast, one study did not show a benefit with corticosteroid administration . Inclusion criteria for this study required any vasopressor use for a minimum of 4 hours, and total mortality rate was 28.3%.…”
Section: Corticosteroidsmentioning
confidence: 90%
“…The benefits of low‐dose corticosteroids on shock reversal were first reported in 1991 . Since then, numerous RCTs have evaluated the effect of low‐dose steroids on shock reversal and mortality (Table ) . Although there are some differences in the regimens used (dose and duration), the method for administration (bolus vs continuous infusion), and the use of a taper, these studies have collectively shown an improvement in shock reversal with low‐dose steroid therapy.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…cortisone per day, over a longer duration of up to 7 days, reduced time-to-vasopressor withdrawal and in some cases mortality, with a tendency for those with lower cortisol response to cosyntropin to show the most benefit32 . In 2018, two large randomized control studies of hydrocortisone in septic shock were published 34,35. In one study, hydrocortisone 200 mg per day did not reduce 90-day mortality; however, there was improved time to shock resolution, and reduced length of time to discharge from both intensive care and hospital 35.…”
mentioning
confidence: 99%
“…In 2018, two large randomized control studies of hydrocortisone in septic shock were published 34,35. In one study, hydrocortisone 200 mg per day did not reduce 90-day mortality; however, there was improved time to shock resolution, and reduced length of time to discharge from both intensive care and hospital 35. Another study did find reduced mortality and reduced vasopressor use in patients who received hydrocortisone and fludrocortisone 34.…”
mentioning
confidence: 99%
“…and the CORTICUS group, enrolling 300 and 500 patients, respectively. The recently completed ADRENAL trial recruited 3800 patients with septic shock and invasive ventilation from four countries (70% from Australia), and examined the effect of hydrocortisone continuous infusion (200 mg/day in ICU). Hydrocortisone was not found to improve mortality in the entire cohort or in any pre‐specified subgroup.…”
Section: Haemodynamic Organ Supportmentioning
confidence: 99%